The use of student assessment data by the teacher to determine the results of learning arts and culture - Lestari Nur Safitri; Yos Sudarman (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
The use of student assessment data to determine the results of learning arts and culture in class VII.1 SMP Negeri 25 Padang which is directly carried out by the supervising teacher and the selection of appropriate material by the teacher, providing corrections at each meeting and providing motivation and praise to students during learning arts and culture using Geschool media on the material Decorative Variety on Wood is the right way to improve student learning outcomes in class VII.1 SMP Negeri 25 Padang. The purpose of this research is to describe the process of using student assessment data by teachers to determine the results of learning arts and culture at SMP Negeri 25 Padang. The theory used in this study is the theory of Bloom's Taxonomy 1956. Learning outcomes within the framework of the study are achieved through three categories of domains, cognitive, affective and psychomotor. This qualitative research uses research with descriptive methods. Using data through documentation, observation, and interviews. The results of the study have described that the use of student assessment data by teachers to determine the results of learning arts and culture through geschool has increased so that from the first meeting the attendance of students was only 72%, at the second meeting was 82 %, the third meeting was 97%, and at the fourth meeting it was 100%, so that the average attendance of students was 88% in arts and culture learning materials for discussing decoration on wood